Geo-Congress 2023. selected papers from sessions of Geo-Congress 2023, March 26-29, 2023, Los Angeles, California - Rathje, Ellen M.; Montoya, Brina; Wayne, Mark H. (American Society of Civil Engineers, 2023)
This is second volume of six Geotechnical Special Publications (GSPs) containing papers from the 2023 Geo-Congress: It includes 69 peer-reviewed papers on topics related to soil improvement, including: carbon footprint of construction; geoenvironmental engineering; soil improvement; sustainability in geotechnical engineering; and sustainable design, equity, and social justice.
Sponsored by the Geo-Institute of the American Society of Civil Engineers.
Keywords: Geotechnical engineering -- Congresses.; Environmental geotechnology -- Congresses.; Soil mechanics -- Congresses.; Sustainable engineering -- Congresses.; elektronické knihy; electronic books